PEMANFAATAN KALENG ALUMINIUM BEKAS DALAM MENANGANI PENCEMARAN AIR - WIWIK SUSANAH RITA; I.A. RAKA ASTITI ASIH; WAHYU DWIDJANI S; I W. SUIRTA; I G.A. KUNTI SRI PANCA DEWI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2008)
ABSTRACT Community service by giving a lecture and practical work with a title: “Utilizing of Aluminum Cans used for Water Purification (Pemanfaatan Kaleng Aluminium Bekas dalam Upaya Penjernihan Air)” was be held on Wednesday, 22nd of August 2007. The participants of this activity were about 45 of the Third degree Students of SMAN Abiansemal Badung. The aim of the activity was to give information that aluminum cans can be recycled into alum (tawas), where it can be used for water purification. The result of this activity indicated that the knowledge of the students have broaden. This was showed by Their enthusiastic to give some questions and ideas. They paid attention about the environmental cleanliness, so this activity can help them to solve many environmental problems and motivate them to run a private enterprise.